Risk Factors for Severe Violence in Intimate Partner Stalking Situations: An Analysis of Police Records - Bendlin, M.; Sheridan, Lorraine (2019)
Stalkers can be violent, and empirical studies have sought to identify factors associated with violence perpetrated by the stalker. Most of these works view physical violence as a homogeneous construct and do not differentiate between moderate and severe violence. The present study aims to identify correlates of nonviolent, moderate, and severe physical violence within an archival sample of 369 domestically violent police incident reports, where stalking behavior was indicated. The incident reports utilized in this study occurred between 2013 and 2017, among intimate or ex-intimate partners. The present study explored 12 independent variables that have yielded mixed findings in previous stalking violence literature, as well as two previously untested factors of nonfatal strangulation and child contact. The police records were coded for severity of physical violence using the Revised Conflict Tactics Scale and analyzed using a logistic regression. The regression analysis revealed significant independent associations between the outcome variable of severe physical violence and child contact, history of domestic violence, separation, nonfatal strangulation, jealousy, previous injury, and victim belief of potential harm. These results may help produce pragmatic recommendations for law enforcement agencies and other relevant bodies who seek to identify victims at risk of severe violence, increasing the potential for early intervention and prevention of physical harm. The awareness of factors that are shown to be related to serious physical violence may assist first responders in recognizing which victims may be at risk of serious harm, as well as effectively allocating any appropriate resources to reduce and prevent harm.